The relationship between the level of economic development, the scale of youth football development and competitive strength in Chinese provinces - Shi, Peng; Hu, Shunding; Zhang, Ziyun (PLOS ONE, 2026)
This study aims to explore the relationship between the economic development level of Chinese provinces, the scale of youth football development, and competitive strength. The data are derived from 31 provinces of China (excluding Hong Kong, Macao, and Taiwan). Indicators of economic development level include GDP, per capita GDP, per capita disposable income, and per capita consumption expenditure. Indicators of the scale of youth football development include the number of featured schools, the number of campus football fields, the level of football clubs in the three-tier league system, the number of social brand youth training institutions, and the number of sports schools. Indicators of youth football competitive strength include the number of top teams and elite teams in the Chinese Youth Football League. The study found that after controlling for total population size and youth population size, per capita disposable income showed a marginally significant positive correlation with both the number of top teams (r = 0.320, P = 0.091) and the number of elite teams (r = 0.359, P = 0.056); GDP (r = 0.458, P = 0.012), per capita GDP (r = 0.466, P = 0.011), per capita disposable income (r = 0.414, P = 0.026), and per capita consumption expenditure (r = 0.412, P = 0.026) all exhibited a moderately significant positive correlation with the number of social youth training institutions; per capita disposable income (r = −0.469, P = 0.010) and per capita consumption expenditure (r = −0.448, P = 0.015) showed a moderately significant negative correlation with the number of featured schools; the level of clubs in the three-tier league system displayed a highly significant positive correlation with both the number of top teams (r = 0.648, P < 0.001) and the number of elite teams (r = 0.778, P < 0.001); and the number of featured schools had a weakly significant negative correlation with the number of top teams (r = −0.369, P = 0.049). In addition, the level of clubs in the three-tier league system played a mediating role between economic indicators and competitive strength. The above research findings can provide a scientific basis for the Chinese government to optimize football policy orientations and the allocation of financial resources.